2017
DOI: 10.1590/0104-6632.20170342s20150541
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, pH and carbon source affect drastically indole acetic acid production of plant growth promoting yeasts

Abstract: -Rhizosphere and phylloplane yeasts are able to produce phytohormones, acting as potential plant growth promoters. The aim of this study was to analyze the production of indole acetic acid (IAA) by yeasts using variations in the culture conditions. The yeasts evaluated were Rhodotorula mucilaginosa and Trichosporon asahii, which were cultivated in a potato broth medium with 20 g/L of glucose or sucrose as the carbon source. The cultivation was carried out at 22°C, 25°C or 30°C, and the initial pH was adjusted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
(45 reference statements)
0
17
1
3
Order By: Relevance
“…It has been reported that both auxin (e.g. Limtong et al, 2014; Streletskii et al, 2016) and zeatin (this study) synthesis in culture varies between species and strains, and may depend on culture conditions (Scarcella et al, 2017). At present, our observations are more relevant for a targeted isolation of yeasts producing plant growth promoters than for plant and yeast ecologists.…”
Section: Discussionmentioning
confidence: 75%
“…It has been reported that both auxin (e.g. Limtong et al, 2014; Streletskii et al, 2016) and zeatin (this study) synthesis in culture varies between species and strains, and may depend on culture conditions (Scarcella et al, 2017). At present, our observations are more relevant for a targeted isolation of yeasts producing plant growth promoters than for plant and yeast ecologists.…”
Section: Discussionmentioning
confidence: 75%
“…These studies reported an average production of 10.6 g.ml -1 after five days and 45 g.ml -1 after seven days of cultivation, respectively. Thus, our results highlight two important issues related to the production of IAA by yeasts: first, varying results are obtained from diverse strains of the same species, especially if they are isolated from different environments (soil, rhizosphere, or phyllosphere); secondly, the specific conditions necessary for the IAA production, such as sources of nutrients and pH of the medium may influence the production significantly, even preventing it (Apine and Jadhav, 2011;Scarcella et al, 2017).…”
Section: Resultsmentioning
confidence: 89%
“…Akan tetapi, dalam penelitian ini tidak dilakukan identifikasi terhadap isolat khamir yang digunakan, sehingga tidak diketahui genusnya. IAA pada beberapa jenis khamir berfungsi untuk membentuk filamen yang berguna untuk invasi serta pemanjangan hifa/pseudohifa untuk memperluas daerah penyerapan nutrisi [16]. Contohnya pada Saccharomyces cerevisae, IAA berfungsi sebagai sinyal untuk mengatur filamentasi yang berfungsi untuk invasi.…”
Section: A Hasil Uji Kualitatif Dan Kuantitatif Isolat Khamir Dalam unclassified
“…Sehingga, ada kemungkinan pada hari ke-4 dan ke-5, sel telah memasuki fase stasioner. Peningkatan produksi IAA pada fase stasioner pada khamir berhubungan dengan menurunnya sumber karbon untuk memenuhi kebutuhan nutrisi bagi metabolisme sel [16].…”
Section: A Pengaruh Lama Waktu Inkubasi Terhadap Produksi Iaa Dan Maunclassified